2004
DOI: 10.5840/beq20041417
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Special E-Commerce Ethics?

Abstract: Abstract:The speed and degree to which e-commerce is infiltrating the very fabric of our society, faster and more pervasively than any other entity in history, makes an examination of its ethical dimensions critical. Though ethical lag has heretofore hindered our explorations of e-commerce ethics, it is now time to identify and confront them. In this paper we define e-commerce and describe the characteristics that set it apart from traditional brick and-mortar business. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
(24 reference statements)
0
33
0
1
Order By: Relevance
“…These dimensions have significant and direct effects on relationship quality (trust and satisfaction) and indirect effect on buyer repurchase intentions and loyalty. Second, this study empirically verifies the argument by Kracher and Corritore (2004) that e-commerce ethics and brick-andmortar business ethics are fundamentally the same. The Internet is continually evolving and multifaceted, therefore ethical issues have different manifestations in e-commerce contexts.…”
Section: Theoretical Implicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…These dimensions have significant and direct effects on relationship quality (trust and satisfaction) and indirect effect on buyer repurchase intentions and loyalty. Second, this study empirically verifies the argument by Kracher and Corritore (2004) that e-commerce ethics and brick-andmortar business ethics are fundamentally the same. The Internet is continually evolving and multifaceted, therefore ethical issues have different manifestations in e-commerce contexts.…”
Section: Theoretical Implicationsmentioning
confidence: 83%
“…Schlegelmilch and Oberseder (2010) showed that ethical issues involving the Internet are privacy, identity theft, and phishing. In exploring specific e-commerce ethics, Kracher and Corritore (2004) examined the key issues of access, intellectual property, privacy and informed consent, protection of children, information security, and trust. Miyazaki and Fernandez (2001) assessed customers' concerns regarding online shopping.…”
Section: Theoretical Background and Development Of Theoretical Framewmentioning
confidence: 99%
“…Marcoux, 2003) and e-commerce (e.g. Kracher and Corritore, 2004) all bear witness to the impact of technological developments on marketing during the recent past. At the same time, the discussion of these ethical issues in academic journals has expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that information produced through the social interaction of individuals facilitated by social media establishes trust for customers; the influence of this information is greater than that offered by a company (Hajli et al 2014). Trust is a challenging factor in an online context (Kracher and Corritore 2004) and research shows trust is associated with eWOM behaviour (Chu and Kim 2011). Recent studies show that trust and issues around security in cyber space are important elements in the development of these platforms (Featherman and Hajli 2015).…”
Section: Introductionmentioning
confidence: 99%